Three-dimensional architectural and structural analysis—a transition in concept and design from Delaire's cephalometric analysis - Lee, S.-H.; Kil, T.-J.; Park, K.-R.; Kim, B.C.; Kim, J.-G.; Piao, Z.; Corre, P. (International Journal of Oral and Maxillofacial Surgery, 2014)
The aim of this study was to present a systematic sequence for three-dimensional (3D) measurement and cephalometry, provide the norm data for computed tomography-based 3D architectural and structural cephalometric analysis, and validate the 3D data through comparison with Delaire's two-dimensional (2D) lateral cephalometric data for the same Korean adults. 2D and 3D cephalometric analyses were performed for 27 healthy subjects and the measurements of both analyses were then individually and comparatively analyzed. Essential diagnostic tools for 3D cephalometry with modified definitions of the points, planes, and measurements were set up based on a review of the conceptual differences between two and three dimensions. Some 2D and 3D analysis results were similar, though significant differences were found with regard to craniofacial angle (C1–F1), incisal axis angles, cranial base length (C2), and cranial height (C3). The discrepancy in C2 and C3 appeared to be directly related to the magnification of 2D cephalometric images. Considering measurement discrepancies between 2D and 3D Delaire's analyses due to differences in concept and design, 3D architectural and structural analysis needs to be conducted based on norms and a sound 3D basis for the sake of its accurate application and widespread adoption.